The Influence of Job Characteristics and Organizational Perception Support on Employee Engagement Statistisi at the Statistics Indonesia - Purba, Rey Ronald; Hendrian, Hendrian; Rahayu, Heffi Christya (Jurnal Ilmiah Sumber Daya Manusia, 2023)
This research would like to see the effect of Job Characteristics variables and perceptions of organizational support on Employee Engagement Statististis at the Statistics Indonesia. This  is  a quantitative research  with primary data collected  from  a  sample  of  429  respondents spread throughout Indonesia (34 provinces),  selected  using  a Systematic Random Sampling  method  through  a  survey  method.  The  data collected were analyzed using a Likert scale of 1-5. In addition, the data were analyzed using multiple linear regression with the aid of SPSS For Windows. The variables of job characteristics and perceived organizational support have a significant effect on employee engagement statistisi at Statistics Indonesia. This study provides a new perspective on job characteristics and perceived organizational support simultaneously have a significant effect on employee engagement statistisi which has never been carried out in previous literature.